Inflammatory demyelinating polyneuropathy versus leptomeningeal disease following Ipilimumab. Issue 1 (30th January 2018) - Cafuir, Lorraine; Lawson, David; Desai, Nilesh; Kesner, Vita; Voloschin, Alfredo
Abstract : Background: Ipilimumab is an FDA-approved anti-CTLA-4 monoclonal antibody used in treatment of metastatic melanoma. We present an unusual neurological complication of Ipilimumab therapy and the diagnostic dilemma it caused. Case presentation: A 42 year old male with Stage IV metastatic melanoma developed lower extremity weakness and sensory neuropathy following three doses of Ipilimumab. MRI of the lumbar spine was initially interpreted as diffuse leptomeningeal disease, and patient began Dexamethasone and radiation with improvement in symptoms. However, subsequent completion imaging revealed smooth nerve root involvement with sparing of the spinal cord, findings more compatible with inflammatory demyelinating polyneuropathy. The absence of malignant cells in the cerebrospinal fluid (CSF) and nerve conduction study (NCS) showing lumbar polyradiculoneuropathy with axonal involvement and demyelinating features supported the diagnosis of inflammatory demyelinating polyneuropathy. Later in the course of his disease, the patient developed frank leptomeningeal melanoma. Conclusion: Ipilimumab immune-related toxicity presented as inflammatory demyelinating polyneuropathy, which was difficult to distinguish from leptomeningeal disease, a common complication of melanoma.